The notion of "adjective" in Dhao; A language spoken in eastern Indonesia - Balukh, Jermy I. (Wacana, Journal of the Humanities of Indonesia, 2015)
It is cross-linguistically defined that adjective is a word category that typically denotes quality and attributes. This category basically falls into semantic properties denoting age, dimension, values, and colours. They also indicate human propensities, physical properties, and speed. Syntactically, adjective typically functions as noun modifiers. However, many adjectives also share features with verbs and/or nouns. This makes adjectives not easy to define. Therefore, morphological and syntactic accounts are required, in addition to semantics, to define the prototypical characteristics of adjectives. This paper has shown that majority of lexemes denoting adjectival properties in Dhao share features with verbs. Although the prefix pa- can be attached to verbs and adjectives to generate causative meaning, adjectives are confined only to the second verb in serial verb construction, instead of being the predicate heads. Further, only four adjectives can function as noun modifiers in their bare forms. These latter adjectives are considered as pure or simple adjectives, while the other nine qualifying for adjectives as "recategorized" adjectives.